Demo: Traffic Splitting for Tor – A Defense against Fingerprinting Attacks - Reuter, Sebastian; Hiller, Jens; Pennekamp, Jan; Panchenko, Andriy; Wehrle, Klaus (Electronic Communications of the EASST, 2021)
Website fingerprinting (WFP) attacks on the anonymity network Tor have become ever more effective. Furthermore, research discovered that proposed defenses are insufficient or cause high overhead. In previous work, we presented a new WFP defense for Tor that incorporates multipath transmissions to repel malicious Tor nodes from conducting WFP attacks. In this demo, we showcase the operation of our traffic splitting defense by visually illustrating the underlying Tor multipath transmission using LED-equipped Raspberry Pis.